A survey of barriers to screening for oral cancer among rural Black Americans. Issue 3 (30th September 2013) - Shepperd, James A.; Howell, Jennifer L.; Logan, Henrietta
Abstract Objective Research documents a disparity between Black and White Americans in mortality for oral cancer that appears to result in part from behaviors such as lower oral cancer screening among Black Americans. We examined barriers to oral cancer screening among Black Americans. Methods We surveyed Black Americans (N = 366) living in rural Florida to identify barriers to getting screened for oral cancer. Results Low knowledge/social attention, lack of resources, and fear/defensive avoidance predicted screening intentions, with lack of resources emerging as the largest barrier. Participants also reported that a recommendation from their provider was most likely to increase screening intentions, whereas encountering financial barriers was most likely to decrease screening intentions. Conclusions Low knowledge/social attention, lack of resources, and fear/defensive avoidance emerged as independent barriers to oral cancer screening, with the latter two barriers accounting for the most variance in intentions to get screened. Copyright © 2013 John Wiley & Sons, Ltd.